2015
DOI: 10.1248/bpb.b15-00364
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Histone Deacetylase 6 Activity <i>via</i> <i>S</i>-Nitrosylation

Abstract: Nitric oxide (NO) is a gaseous regulatory factor produced by NO synthases (NOS) and it plays several critical roles via S-nitrosylation of protein cysteine residues. Histone deacetylase (HDAC) functions in the maintenance/balance of chromatin acetylation and contributes to transcriptional supression. It has been reported that S-nitrosylation of HDAC2 is involved in the regulation of deacetylase activity. However, it remains unknown whether other subtypes of the HDAC family are S-nitrosylated. In the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…[10][11][12] MIF acts as a ligand for the type II transmembrane receptor, the CD74/ CD44 complex, to activate the phosphatidylinositol 3-kinase (PI3K)/Akt and p38 mitogen-activated protein kinase (MAPK) signaling pathways, which induce the expressions of brainderived neurotrophic factor (BDNF). [13][14][15][16] Here, we show that MIF is S-nitrosylated by a physiological NO donor. We also determined that the induction of S-nitrosylation resulted in a loss of MIF activities, such as the stimulation of PI3K/Akt and p38 MAPK signaling pathways, and the induction of BDNF expression.…”
Section: Introductionmentioning
confidence: 64%
“…[10][11][12] MIF acts as a ligand for the type II transmembrane receptor, the CD74/ CD44 complex, to activate the phosphatidylinositol 3-kinase (PI3K)/Akt and p38 mitogen-activated protein kinase (MAPK) signaling pathways, which induce the expressions of brainderived neurotrophic factor (BDNF). [13][14][15][16] Here, we show that MIF is S-nitrosylated by a physiological NO donor. We also determined that the induction of S-nitrosylation resulted in a loss of MIF activities, such as the stimulation of PI3K/Akt and p38 MAPK signaling pathways, and the induction of BDNF expression.…”
Section: Introductionmentioning
confidence: 64%
“…Alternatively, methods to target the upstream regulators of HDAC6 could indirectly decrease its protein levels and reduce deacetylase and E3 ubiquitin ligase activity. For instance, tamoxifen treatment of MCF-7 breast cancer cells prevented estradiol-stimulated HDAC6 accumulation and α-tubulin deacetylation [ 57 ], and nitric oxide (NO) is able to increase the acetylation of α-tubulin in A549 cells by preventing the essential S-nitrosylation of HDAC6 [ 58 ]. More directly, Cullin 3SPOP has been reported to destabilize HDAC6 via polyubiquitination, and this interaction has suggested that SPOP serves a tumor suppressor function through this mechanism [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Hdac1 and Hdac2 are differentially regulated by numerous post-translational modifications (PTMs) 17 . Hdac1 has been reported phosphorylated, acetylated, SUMOylated, and ubiquitinylated, while Hdac2, similarly to Hdac6 18 , was also found S-nitrosylated. Surprisingly, in skeletal muscle, Hdac2 S-nitrosylation seemed to have negative effects on the function of both Hdacs 10 .…”
Section: Introductionmentioning
confidence: 94%